Cellular and humoral immune response to SARS-CoV-2 mRNA vaccines in patients treated with either Ibrutinib or Rituximab - Bacova, Barbora; Kohutova, Zuzana; Zubata, Ivana; Gaherova, Lubica; Kucera, Petr; Heizer, Tomas; Mikesova, Marcela; Karel, Tomas; Novak, Jan (Clinical and Experimental Medicine, 2023)
Patients treated with B-cell-targeting therapies like Rituximab or Ibrutinib have decreased serological response to various vaccines. In this study, we tested serological and cellular response to SARS-CoV-2 mRNA vaccines in 16 patients treated with Ibrutinib, 16 treated with maintenance Rituximab, 18 patients with chronic lymphocytic leukaemia (CLL) with watch and wait status and 21 healthy volunteers. In comparison with the healthy volunteers, where serological response was achieved by 100% subjects, patients on B-cell-targeting therapy (Ibrutinib and Rituximab) had their response dramatically impaired. The serological response was achieved in 0% of Rituximab treated, 18% of Ibrutinib treated and 50% of untreated CLL patients. Cell-mediated immunity analysed by the whole blood Interferon-γ Release immune Assay developed in 80% of healthy controls, 62% of Rituximab treated, 75% of Ibrutinib treated and 55% of untreated CLL patients. The probability of cell-mediated immune response development negatively correlates with disease burden mainly in CLL patients. Our study shows that even though the serological response to SARS-CoV-2 vaccine is severely impaired in patients treated with B-cell-targeting therapy, the majority of these patients develop sufficient cell-mediated immunity. The vaccination of these patients therefore might be meaningful in terms of protection against SARS-CoV-2 infection.
Keywords: buněčná imunita; Rituximab; Vaccination; Leukemia, Lymphocytic, Chronic, B-Cell; COVID-19; protokoly protinádorové kombinované chemoterapie; vakcinace; Humans; vakcíny proti COVID-19; SARS-CoV-2; lidé; rituximab; Immunity, Humoral; Immunity, Cellular; humorální imunita; Antineoplastic Combined Chemotherapy Protocols; chronická lymfatická leukemie; COVID-19 Vaccines